What have we learnt from Vioxx? - Krumholz, Harlan M (BMJ Publishing Group Ltd., 2007)
In October UK patients who had cardiovascular events while taking rofecoxib lost the right to fight Merck in the US for compensation. But researchers and journals can still benefit from this case if they learn from the mistakes, write Harlan Krumholz and colleagues